2016
DOI: 10.7146/tjcp.v3i1.23646
|View full text |Cite
|
Sign up to set email alerts
|

Exchanging Engagement: Alternative Arts Engagement in Latin America

Abstract: In 1973, Eduardo Galeano (1940-2015), the Uruguayan writer and journalist concluded his seminal book Open Veins of Latin America with the following: ‘The Latin American cause is above all a social cause: the rebirth of Latin America must start with the overthrow of its masters, country by country. We are entering times of rebellion and change’ (Galeano, 1973, p. 261). As Galeano stated, the oppression of populations and the loss of lives throughout Latin America led to ‘times of rebellion and change’. Artists,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In an international context, research on young people's cultural participation explores the potential of ameliorating young people's supposed detachment from politics by having them participate in different art forms (Elliott 2016;Selwood, 1997;Zobl & Huber, 2016), while others challenge the perception of young people as politically detached (de Roeper & Savelsberg, 2009). A study on Danish students' understandings and experiences of participation showed that young people understand participation in ways that blur dualities of "personal and political, private and public, power and identity" (Eriksson 2016: 171).…”
Section: Participation and Young Peoplementioning
confidence: 99%
“…In an international context, research on young people's cultural participation explores the potential of ameliorating young people's supposed detachment from politics by having them participate in different art forms (Elliott 2016;Selwood, 1997;Zobl & Huber, 2016), while others challenge the perception of young people as politically detached (de Roeper & Savelsberg, 2009). A study on Danish students' understandings and experiences of participation showed that young people understand participation in ways that blur dualities of "personal and political, private and public, power and identity" (Eriksson 2016: 171).…”
Section: Participation and Young Peoplementioning
confidence: 99%